Beyond the Meaning of Pain: Optimal Pain Assessment Tools for (Unable to Self-Report) Critically Ill Patients: A Narrative Review - Benkafo, Abeer; Aladah, Rawan; Aloufi, Nouf Abdulrahman; AL-jezani, Eman Mousa; Aljezani, Fardous Mousa; Alamri, Sameeha Salamah Saleem; H. Alshaeri, Amal Abdu; Aljezani, ⁠Fatmah Mousa; Basri, Zakyah Hashem (Journal of Ecohumanism, 2024)
Pain and its recognition can be complex issues for critical care nurses and their patients. More than half of critically ill patients have unrecognised/undertreated pain, or under/overestimated pain, which have serious physical and psychological impacts and may delay recovery. Many studies have focused on tools for assessing pain rather than on ways of prioritising pain recognition and management. Since ineffective clinical judgement (pain assessment and recognition) and decision-making (pain management) lead to increased morbidity and mortality among critically ill patients, pain recognition should be a priority in all clinical situations. The present study will justify the importance of pain assessment tools in pain management by reviewing the literature. Many studies identified challenges of pain assessment for (difficult to assess) patients such as patients with intellectual disabilities or tested one or two of the pain assessment tools validities. However, none of these studies considered gathering all tools to identify, describe and compare the appropriate tool(s) validity and reliability for the unable to self-report critically ill patients. So, this study will be the first to cover this literature gap and go beyond the challenges and meaning of pain in critical care.